Analysis of The Impact of Company Existence Related to Tax Holiday and Allowance - Asmin, Erny Amriani; Gemina, Dwi; Gemini, Pra; Hutajulu, Immanoel Gunawan; Mashadi, M.; Hutajului, Richard Surungan (Golden Ratio of Taxation Studies, 2025)
This study aims to analyze the impact of a company’s existence receiving tax holidays and allowances on the surrounding community. Data were collected from the community around the company, local government, and management and analyzed descriptively. The sample comprises 10 people from the community around LNK, Mojokerto local government, and company representatives. Similarly, data were collected from 10 communities around EOJI located in Gresik, a representative from the local government and the company using the Non- Probability Accidental Sampling technique. They were then classified to obtain an overview of the total impact of the two companies receiving TA and TH, with 50%, 30%, and 20% weight from the perspective of the surrounding community, regional government, and the company, respectively. The results showed that LNK has an impact of 82.96 with a good category, thus, it is recommended as a good company with a positive and significant impact on the community. EOJI is only 67.35% and can not be recommended to get TA and TH because the benefits are not significant enough for the surrounding community. This study recommends that the government, as the policyholder in the provision of TA and TH, pay more attention to the impact of the company’s existence from the Social, Economic, CSR, and Environmental aspects. Further studies should be conducted on different companies receiving to determine the policy effectiveness of giving TA and TH.